The impact of cultural industries on national economy / Herwina Rosnan and Mohd Nazari Ismail - Rosnan, Herwina; Ismail, Mohd Nazari (Institute of Business Excellent and University Publication Center (UPENA), 2010)
The main objective of this paper is to examine the impact of cultural industries in general and film industry in particular on national economy. Globally, cultural industries have contributed to economic development of many developed and developing countries. For example, in the United States, film industry (which fall under the category of cultural industries) contribution is greater than its aerospace industry. In the case of third world countries, film industry has been neglected in the academic literature despite its huge potential contribution to the economy. Based on the reviews of earlier studies, it was found that little attention has been given by scholars to study the impact of cultural industries and national economic development. Most studies on economic development focused on other industries deemed significant, especially manufacturing industry. Hence, this paper highlights the importance of cultural industries and its potential contribution to national economy. It also highlights some important points that need to be considered by national government in their effort to benefit from the development of their national film industry.